(untitled) (Revista científica Olimpia, 2024)
This article is part of ongoing doctoral research. Its objective is to present the results of applying a strategy for the didactic management of teachers of the subject Gynecology and Obstetrics in contingency situations. The shortcomings detected are corroborated from the initial verification applied to a sample of 17 teachers of said subject who worked during the COVID-19 epidemic with whom the proposed strategy was developed. The theoretical methods used were analysis and synthesis, historical-logical and induction-deduction. Observation and survey were used as empirical methods. The interview and questionnaire were used as techniques. Percentage analysis was used as a statistical-mathematical method. The strategy for the didactic management of the teachers of the subject Gynecology and Obstetrics in contingency situations was structured in four stages in correspondence with the dimensions that have been the object of study, which respond to the problems identified during the investigation and evidenced, through critical opinion and collective construction workshops, the feasibility of its application.